﻿The insistent realism of Don DeLillo’s ‘Falling Man’ and Paul Auster’s ‘Man in the Dark’ (Altre Modernità, 2011)
Many scholars considered that the fictionalization of September 11 marked the apotheosis of the postmodern era of images and perception. At the same time, the WTC collapse inspired a kind of post 9/11 fiction characterised by strong realistic descriptions. The aim of this article is to understand how Don DeLillo's Falling Man (2007) and Paul Auster's Man in The Dark (2008) tried to find a way to present, through a complex recourse to realism, the uncanny events of 9/11 and its prolonged aftermath that culminated in the subsequent horrors of the Iraq war. The insistent assertion of a proper representation of the traumatic events explictly contrasts the evasive literary narrations and the imaginary counter-narratives that might erode the relevance of the events. Furthermore, the detailed representation of these tragedies opposes itself to the equally insistent aesthetics of terror, through a revaluation of what the American literary theorist Ihab Hassan correctly defined (with no religious implications) a “postmodern aesthetic of trust”, that “brings us to a fiduciary realism, a realism that redefines the relation between subject and object, self and other, in terms of profound trust.”